Experimental and Theoretical Investigations on Thermal Conductivity of the Paraffin Wax using CuO Nanoparticles. (2020) - Manoj Kumar, P.; Anandkumar, R.; Sudarvizhi, D.; Mylsamy, K.; Nithish, M.
Abstract: This paper presents the investigations on improving thermal conductivity of the paraffin wax using copper oxide (CuO) nanoparticles to be used an efficient thermal energy storage material. Five samples of paraffin wax were synthesized by dispersing 0, 0.5, 1.0, 1.5, and 2.0 weight percentages of CuO nanoparticles in paraffin wax. Surface microstructures of the samples were examined under field emission scanning electron microscope (FESEM). Thermal conductivity was calculated by both experimental and theoretical methods for the prepared samples. The results revealed that thermal conductivity was improved substantially with the increasing content of CuO nanoparticles in paraffin wax. Explicitly, thermal conductivity of the solid phase paraffin wax is improved drastically, compared to that of liquid phase. However, the experimental values of thermal conductivity is higher than the values obtained through the theoretical models, because theoretical models are not compatible to accommodate the variation in size, shape and surface properties of the nanoparticles